The impact of transgenesis on mosquito fitness: A review - Dilani, Padukka Vidanelage Desha; Dassanayake, Ranil Samantha; Tyagi, Brij Kishore; Gunawardene, Yasanthi Illika Nilmini Silva (Frontiers in Insect Science, 2022)
Transgenic mosquitoes based on genetic manipulation offer a promising strategy for the sustainable and effective control of mosquito-borne diseases. This strategy relies on the mass release of transgenic mosquitoes into the field where their transgene is expected to persist in the natural environment either permanently or indefinitely in the mosquito population. The fitness of transgenic mosquitoes is an important factor in determining the latter mosquito’s survival in the field. The impact of the transgene expression, insertional mutagenesis, selection related to laboratory adaptation, inbreeding depression and hitchhiking effect involved in developing homozygous mosquito lines can all have an effect on the fitness of transgenic mosquitoes. Therefore, the real estimation of transgene-associated fitness cost is essential for modeling and planning transgenic mosquito release programs. This can be accomplished through direct comparisons of fitness parameters of the individuals homozygous for the transgene with their non-transgenic counterpart, comparison of fitness parameters of individuals hemizygous for the transgene with their wild type counterparts or cage invasion experiments to monitor frequency of the transgenic allele over multiple generations. Furthermore, more research on the fitness of transgenic individuals is required in order to develop transgenic mosquitoes with law fitness cost